Sclerostin - Stuart L. Silverman (Journal of Osteoporosis)
The striking clinical benefits of intermittent parathyroid hormone in osteoporosis have begun a new era of skeletal anabolic agents. One potential new agent is monoclonal antibody to sclerostin, a potent inhibitor of osteoblastogenesis.